(untitled) (Majalah Kedokteran Bandung, 2026)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder associated with synaptic dysfunction and chromatin remodeling abnormalities. Among the genes implicated in ASD, SHANK3 and CHD8 play essential roles in synaptic organization and neurodevelopmental regulation. This study aimed to investigate genetic variants in SHANK3 and CHD8 and evaluate their possible association with ASD susceptibility. A case-control study was conducted on twenty (20) participants, including ten (10) clinically diagnosed ASD patients according to DSM-5 criteria and ten (10) age- and sex-matched neurotypical controls. Whole-exome sequencing was performed using the Illumina NovaSeq platform with a mean coverage depth of 95× and more than 98% of target regions covered at ≥20×. Detected variants were annotated and analyzed for missense, splice-site, synonymous, and intronic alterations. Structural bioinformatics and protein interaction analyses were applied to assess the biological significance of the identified variants. A total of eighteen (18) variants were detected in SHANK3 and CHD8 genes. Two variants showed higher frequencies in ASD patients, including a missense variant (p.Ile320Thr) and a splice-site variant potentially affecting RNA processing. Structural modeling suggested that the p.Ile320Thr substitution may reduce SHANK3 protein stability. Protein interaction analyses indicated functional connectivity between SHANK3 and CHD8 through NRXN1, SYNGAP1, and GRIN2B pathways. In conclusion, the findings provide preliminary evidence supporting the involvement of SHANK3 and CHD8 variants in ASD pathogenesis through synaptic and chromatin-related mechanisms. Further studies with larger cohorts are recommended to validate these findings.